Comparison of repeated applications of aPDT with amoxicillin and metronidazole in the treatment of chronic periodontitis: A short-term study - Theodoro, Letícia Helena [UNESP]; Lopes, Alessandra Barreto [UNESP]; Nuernberg, Marta Aparecida Alberton [UNESP]; Cláudio, Marina Módolo [UNESP]; Miessi, Daniela Maria Janjacomo [UNESP]; Alves, Márcio Luiz Ferro [UNESP]; Duque, Cristiane [UNESP]; Mombelli, Andrea; Garcia, Valdir Gouveia [UNESP] (Elsevier, 2017)
Aim The aim of this study was to compare the clinical effects of Metronidazole (MTZ) combined with Amoxicillin (AMX) and repeated applications of antimicrobial photodynamic therapy (aPDT) as an adjuvant for the treatment of chronic periodontitis. Methods A double-blind controlled and randomized clinical trial was conducted in 34 patients. All of the patients were treated with scaling and root planing (SRP) and separated into 2 groups: the MTZ + AMX Group (n = 17), who received SRP and the systemic use of MTZ (400 mg 3 × per day for 7 days) and AMX (500 mg 3 × per day for 7 days), and the aPDT Group (n = 17), who received SRP and three aPDT applications at all sites with a probing depth ≥ 5 mm immediately, at 48 and 96 h after scaling and placebo pills over the span of 7 days. Clinical examinations were performed at baseline and 90 days post-therapy. The clinical parameters of bleeding on probing (BOP), probing depth (PD), and clinical attachment level (CAL) were measured. The aPDT was conducted using methylene blue and a low-level laser (GaAlAs 660 nm, 100 mW, 48 s, and 160 J/cm2) in all sites with a probing depth ≥ 5 mm. A statistical analysis was also performed (α = 5%). Results There was a significant improvement in CAL only in the intermediate pocket in the aPDT group compared to the MTZ + AMX group between baseline and 90 days post-treatment (p = 0.01). There was a reduction of both BOP and the percentage of residual pockets at 90 days after treatment compared with baseline in both groups (p < 0.05). Conclusion Both proposed adjuvant therapies associated with conventional mechanical treatment in patients with chronic periodontitis were equally effective in terms of the gain of clinical insertion, control of inflammation and elimination of residual pockets.
Keywords: Antibiotics; Dental Scaling; Periodontitis; Photochemotherapy